2011
DOI: 10.1111/j.1476-5381.2011.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse patterns of cyclooxygenase‐independent metalloproteinase gene regulation in human monocytes

Abstract: BACKGROUND AND PURPOSEMatrix metalloproteinase (MMP) production from monocyte/macrophages is implicated in matrix remodelling and modulation of inflammation. However, knowledge of the patterns and mechanisms of gene regulation of MMPs and their endogenous tissue inhibitors (TIMPs) is fragmentary. MMP up-regulation may be a target for cyclooxygenase (COX) and prostaglandin (PG) receptor inhibition, but the extent and mechanisms of COX-independent MMP up-regulation are unclear.EXPERIMENTAL APPROACHWe studied MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
7
30
0
Order By: Relevance
“…Inflammatory activation stimulates MMP-9 expression in human ECs, VSMCs and monocytes [49] through NF-κB, although human macrophages and FCMs express constitutively high levels ( Fig. 1) [20] similar to those seen in rabbits.…”
Section: Mmp-9mentioning
confidence: 89%
See 1 more Smart Citation
“…Inflammatory activation stimulates MMP-9 expression in human ECs, VSMCs and monocytes [49] through NF-κB, although human macrophages and FCMs express constitutively high levels ( Fig. 1) [20] similar to those seen in rabbits.…”
Section: Mmp-9mentioning
confidence: 89%
“…The enzyme is expressed in human ECs, where it can function to activate MMP-1 [27]. MMP-10 is also expressed in human adhered monocytes [49] and classically-activated macrophages [20] and, like MMP-1, is co-localized in human plaques with COX-2 and nuclear NF-κB. An MMP-10, MMP-1 activation cascade is therefore feasible in human plaques and could give rise to plaque instability.…”
Section: Mmp-10mentioning
confidence: 97%
“…Because PGE 2 production is involved in MMP transcription, antagonists at the PGE 2 receptor could also be useful in stabilizing plaques [191,192]. Aspirin and other cyclooxygenase inhibitors also inhibit MMP production by monocytes [78], although cyclooxygenase independent pathways of MMP production may reduce the beneficial impact of these compounds in man [79]. In addition, MMP-1, -3 and -14 are expressed via NF-B, therefore inhibition of this transcription factor might reduce expression of these MMPs [83].…”
Section: Inhibition Of Metalloproteinases As Therapeutic Strategies Fmentioning
confidence: 99%
“…MMPs are the predominant proteolytic enzymes, thought to participate in weakening the connective tissue matrix in the intima, leading to plaque rupture and acute thrombosis [76,77]. Of note, human peripheral blood monocytes express MMP-8, -9, -14 and -19, TIMP-1 and TIMP-2 constitutively, but activated macrophages and foam cells express high levels of several MMPs, in response to adhesion and pro-inflammatory mediators, either directly, through mitogen-activated protein kinase (MAPK) activation and the NF-B pathway, or indirectly, with prostaglandin E 2 (PGE 2 ) involvement [78,79]. The upregulation of MMP secretion by differentiated macrophages can be stimulated by contact with endothelial cells (ECs) [80] and by adhesion to matrix components, such as collagen [81].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that COX2 and its product prostaglandin directly up-regulated the expression of MMP1. Previously, the expression of the COX2 gene was reported to be regulated by MMP1 in macrophage (49), indicating that both genes are reciprocally controlled by a potential feedback mechanism. Many aggressive cancer cells express high levels of COX2, and this gene has been shown to affect BBB permeability (50).…”
Section: Breast Cancer Mmp1mentioning
confidence: 99%